THE POROSITY CALCULATION OF VARIOUS TYPES OF PAPER USING IMAGE ANALYSIS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
The paper porosity study has been done by observing microscopically.The purpose is provide airborne porosity data on various paper types, so that we can rank the ability of liquid absorption on the same paper type. This porosity analysis is done by using ImageJ, with converting the image to binary, set the threshold limit, and clarify the watershed limit. The result of the porosity of filter paper A=51,50586 , B=18,30719 ,C=21,68076 ,D=29,72028 ; tissue paper A=9,174071 ,B=20,96931 ,C=32,76454 ; HVS paper A=23,31616 ,B=27,70944 . So it can be concluded that the ability of filter paper absorption A filter paper D filter paper C filter paper B. Absorption ability tissue paper C tissue paper B tissue paper A. Absorption ability HVS B paper HVS paper A. In general can be inferred that the higher the porosity value of the paper the greater ability to absorb liquids on paper.